PEMANFAATAN TEKNOLOGI MEDIA DIGITAL DAN ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN DI MAN 3 BANTUL - Dhiyaul Haq Ahmad; Iqbal Saputra; Aditya Dian Saputra; Muhammad Faddli Khairi (STKIP Subang, 2026)
This study aims to describe the use of digital media technology and artificial intelligence (AI) in learning at MAN 3 Bantul and to identify challenges in strengthening students’ digital literacy. This qualitative descriptive study used semi-structured interviews with the Vice Principal of Curriculum. The findings show that digital technology has been integrated into learning through digital applications, AI tools, and digital administrative systems. These practices positively affect students’ engagement, creativity, and learning independence. However, challenges remain related to discipline and ethical use of technology. Therefore, strengthening digital literacy through supervision and continuous guidance is necessary to ensure technology is used effectively and responsibly in supporting meaningful learning.